An analysis of integrated reporting on the governance of selected State-Owned Enterprises (SOEs) - Songxaba, Bathabile Liberty (Rhodes University, Faculty of Commerce, Rhodes Business School)
The research investigated how integrated annual reports (IARs) can enhance the governance of state-owned enterprises (SOEs). Governance of SOEs is crucial to achieving the county's socio-economic objectives. The SOEs listed on Schedule 2 of the Performance Finance Management Act (PFMA), Act No. No.1 of 1999, as amended in March 2017, represents, among many, the electricity, transportation, and telecommunication sectors. This study analysed the integrated reporting (IR) governance of selected schedule 2 of PFMA SOEs. The researcher adopted the qualitative approach for the study. Firstly, the analysis was to identify and describe the governance disclosures as evident in IARs using the King IV principles. Secondly, the study analysed the reporting trends associated with governance practices over 2018 "“ 2020. Integrated reports from Eskom, Transnet, and Telkom were selected for three years. Relevant concepts discussed in the literature review include corporate governance, King reports on corporate governance, King IV principles, the principle of materiality on governance disclosures, corporate reporting, integrated reporting, integrated thinking, benefits of integrated reporting, theoretical underpinnings of the study, and a conclusion. The disclosures were summarised per year and SOE per King IV principle, resulting in nine (9) excel spreadsheets, which were combined excel spreadsheets sorted into a logical structure based on coding to keep track of the source data sequence. The data was systematically manually coded using Ose's (2016) Microsoft Word and Excel method. Findings included seven themes which were ethics, irregular expenditure, internal controls, accountability, governance structures, reputation, and sustainability. Themes were transferred to subtopics for comparative analysis to assess trends and the SOEs' governance disclosures. The results found that all three SOEs have disclosed using King IV principles guided by the 2013 International Integrated Reporting Council's (IIRC) framework. All SOEs disclosed their governance in their reports and practice explained. There are noticeable differences, Eskom and Transnet are solely government-owned, and Telkom is partially privatised and run privately as the majority holding is mostly private. Eskom and Transnet reflected more similarities in terms of their operational and financial challenges, whereas Telkom operates in a more competitive environment and is run as a private company which is portrayed to be profitable and restricted to Johannesburg Stock Exchange (JSE) requirements. Disclosures indicate progress on material matters and links associated with functional areas such as strategy and risks. Materiality is a guiding principle in the IIRC framework, which assist discloses information that significantly affects the organisation's ability to create value over time. The similarities in all three SOEs include challenges in retaining competent and ethical leaders, which is critical for enhancing good governance. The study recommended how the integrated report can be viewed as a management and accounting tool for the governing body and stakeholders to focus on drivers that create value and consider drivers that erode or preserve value. This feedback may assist in informing strategy, business model, and decision-making for the governing body to set governing structures that support the organisation to create sustained value.
Keywords: Government business enterprises Management; Integrated reporting; Integrative thinking; Corporate governance Law and legislation -- South Africa; Good governance; Business ethics -- South Africa